Analisa Pola Produksi Kelapa Sawit Dan Keseimbangannya Terhadap Pabrik Kelapa Sawit Di Pantai Barat Aceh - Aswin Nasution; Fajri Fajri; Sofyan Sofyan (Jurnal Agrisep, 2015)
ABSTRACT. This study was conducted to analyze the balance of palm oil FFB production pattern with raw material needs POF on the west coast of Aceh, how the addition of POF is required. The research method used is Purposive Cluster Sampling with the research object farmers and plantation companies. The results of this study indicate that by assuming no increase in plantation area, the FFB palm oil production patterns on the west coast of Aceh increased until 2022 and subsequently production decreased following the increase in age of the plant. Did not happen balance between FFB production patterns and material requirements POF where there is overbalance production of 490,418 tons of FFB processing capacity of 12 units POF operating today. FFB overbalance of processing capacity of the POF in 2014 requires the addition of 3-6 POF unit capacity of 30 tons / hour with 3 units at 100% of the processing capacity and 6 units at 60% processing capacity. Distribution addition of POF is 1 unit in West Aceh, 1-2 units in Nagan Raya and 2-3 units in Southwest Aceh. FFB overbalance top occurred in 2022 amounted to 1,531,317 tons with the needs 27-34 POF unit capacity of 30 tons / hour. The addition of POF will need to follow the addition of overbalance FFB.